Pengaruh tanggung jawab sosial perusahaan (CSR) dan profitabilitas terhadap nilai perusahaan - Dwijayanti, Linda; Irma, Dasih; Ningsih, Hestin Agus Trantri (Journal of Accounting, Management, and Economics Research (JAMER), 2025)
This study investigates the influence of Corporate Social Responsibility (CSR) and Profitability on Company Value in the Cosmetics and Household Goods industry listed on the Indonesia Stock Exchange from 2015 to 2019. Using a purposive sampling method, six companies were selected. The study relies on secondary data obtained from the Indonesia Stock Exchange, analyzed through regression analysis. Several statistical tests were conducted, including tests for classical assumptions, normality, heteroscedasticity, autocorrelation, correlation coefficient, coefficient of determination, as well as t-tests and f-tests. The results reveal that both CSR and Profitability individually have a significant effect on Company Value. Furthermore, when combined, CSR and Profitability also significantly influence Company Value. These findings suggest that managers in the cosmetics and household goods industry should prioritize CSR initiatives and improve profitability to enhance company value. Companies are encouraged to develop strategies that support environmental and social responsibilities while also increasing operational efficiency to drive profit growth.